Revealing Potential Regional Original Income of Southwest Maluku Regency - Paul Usmany (Journal of Governance, 2022)
This research is designed in an analytical framework that aims to reveal the potential of the Regional Original Income of Southwest Maluku Regency (Southwest Maluku). As it is known that the practice of regional autonomy in Indonesia has been going on for more than two decades, and although each local government has been given wider authority to manage its region by exploring sources of Regional Original Revenue, there is evidence that shows that most areas are still faced with the problem of low Original Regional Revenue, and has not been able to make a significant contribution to regional revenues, including the Southwest Maluku Regency. The analytical method used in this research is the Quantitative Descriptive Analysis Technique and the SWOT Matrix. The results of the analysis of the effectiveness ratio, growth ratio, and contribution ratio show that the achievement of Regional Original Income in Southwest Maluku Regency is not optimal; The low contribution of Regional Original Revenue to regional revenues causes this district to be unable to be categorized as an independent region in meeting the needs of its development financing budget. In addition, the mapping analysis of the growth of the Regional Original Income component shows that Regional Taxes have the highest average growth, followed by Regional Levies, and finally, Other Legitimate Regional Original Income. Meanwhile, the results of the SWOT analysis show that the management of Regional Original Revenue in Southwest Maluku Regency is still weak internally but has many opportunities to be developed; Furthermore, the SWOT Matrix concludes that alternative strategies should be a top priority for efforts to optimize the management of Regional Original Revenue in Southwest Maluku Regency by improving weaknesses in optimizing opportunities.